A run on the biobank: what have we learned about type 1 diabetes from the nPOD tissue repository?. Issue 4 (August 2015) - Kaddis, John S.; Pugliese, Alberto; Atkinson, Mark A.
Abstract : Purpose of review: Since the inaugural year of its biobank in 2007, the Network for Pancreatic Organ Donors with Diabetes program has provided 70 370 human samples to 127 investigators worldwide for projects focused on the pathogenesis of type 1 diabetes (T1D). The purpose of this review was to highlight major advances in our understanding of T1D using works that contain original data from experiments utilizing biospecimens provided by the Network for Pancreatic Organ Donors with Diabetes program. A total of 15 studies, published between 1 June 2013 and 31 December 2014, were selected using various search and filter strategies. Recent findings: The type and frequency of B and/or T-cell immune markers in both the endocrine and exocrine compartments vary in T1D. Enterovirus signals have been identified as having new proteins in the extracellular matrix around infiltrated islets. Novel genes within human islet cell types have been shown to play a role in immunity, infiltration, inflammation, disease progression, cell mass and function. Various cytokines and a complement degradation product have also been detected in the blood or surrounding pancreatic ducts/vasculature. Summary: These findings, from T1D donors across the disease spectrum, emphasize the notion that pathogenic heterogeneity is a hallmark of the disorder.